2020
DOI: 10.3390/cryst10070594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles on the Melting Behavior, Isothermal Crystallization Kinetics and Morphology of Polyoxymethylene

Abstract: In this work, the effects of silver (Ag) nanoparticles on the melting behavior, isothermal crystallization kinetics, and morphology of polyoxymethylene (POM) were studied. It was found that the melting peak temperature (Tm) and the crystallization temperature (TC) of POM/Ag nanocomposites shifted to higher temperature with the content of Ag nanoparticles increased. In addition, the isothermal crystallization kinetics of POM/Ag nanocomposites were determined by Avrami and Lauritzen-Hoffman models. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The melting and crystallization behavior of POM/Ag/MAH-g-POE ternary nanocomposites are shown in Figure 5 and the DSC parameters are given in Table 2. Meanwhile, the melting and crystallization behavior of the POM/Ag nanocomposites can be found in previously published papers [27,28]. As seen in Figure 5, there were no significant changes in the melting peak temperature (T m ) and the crystallization peak temperature (T c ) values of POM/Ag/MAH-g-POE ternary nanocomposites.…”
Section: Dsc Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…The melting and crystallization behavior of POM/Ag/MAH-g-POE ternary nanocomposites are shown in Figure 5 and the DSC parameters are given in Table 2. Meanwhile, the melting and crystallization behavior of the POM/Ag nanocomposites can be found in previously published papers [27,28]. As seen in Figure 5, there were no significant changes in the melting peak temperature (T m ) and the crystallization peak temperature (T c ) values of POM/Ag/MAH-g-POE ternary nanocomposites.…”
Section: Dsc Analysismentioning
confidence: 76%
“…SEM images of POM/Ag/MAH-g-POE nanocomposites are shown in Figure 3. Meanwhile, SEM and TEM images of the POM/Ag nanocomposites can be found in the previously published papers [27,28]. Figure 3a shows the SEM image of POM, and it can be seen that there were no nanoparticles in the POM matrix, and the surface was smooth.…”
Section: Semanalysismentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, studies of composites based on polyoxymethylene by Zeng et al showed that the degree of crystallinity (Xc) increased with an increase in the amount of nano-Ag particles (from 0 to 2% by weight) [ 25 ]. Wacharawichanant et al, in their work, analyzed the effect of the addition of nano-ZnO on the mechanical properties of the POM/nano-ZnO composite.…”
Section: Introductionmentioning
confidence: 99%